The Writing-Machine as Method: Affect, Acker, and the Traumatized Subject. Issue 1 (2nd January 2019) - Johnson, Freya
Abstract : In this article I explore writing as a method of attending to the singularities of life and worlds without thinking in terms of a primordial Whole. Deleuze and Guattari present the writing-machine as that which produces effects and transforms affective experience; the focus is on what use, rather than meaning, the writing has. I extend a discussion of this concept by exploring the generation of my own research space through machinic writing as a technique. I then turn to the development of trauma as the central research topic, and explore the capacity of my still-forming narrative— What Happened to Harriet —to unpick the clinically defined traumatized subject. The narrative illustrates traumatic experience as a chaotic and difficult-to-represent progression of sensations. To add texture to this discussion, I stay close to the work of Kathy Acker, whose own writing, often centered on trauma, exemplifies a fragmented, disruptive, and anti-Oedipal writing-machine.